On the Mechanical and Thermal Properties of Poly(Vinyl Alcohol) – Alginate Composite Yarn Reinforced with Nanocellulose from Oil Palm Empty Fruit Bunches - Ainul Maghfirah; Farah Fahma; Nurmalisa Lisdayana; Muchammad Yunus; Ahmad Kusumaatmaja; Grandprix Thomryes Marth Kadja (Universitas Gadjah Mada, 2022)
PVA-alginate hydrogel is a promising material for use in biomedical applications due to its desirable characteristics: biocompatible, durable, non-toxic, and low cost. However, the low gel strength of this composite limits its use in biomedical applications. This study aims to develop enhanced mechanical and thermal properties of poly(vinyl alcohol) PVA-alginate composite yarn by adding nanocellulose isolated from the sustainable oil palm empty fruit bunches (OPEFBs). The PVA-alginate composite yarns reinforced with nanocellulose were prepared with various nanocellulose contents (1 wt.%, 2 wt.%, and 5 wt.%). The composite's tensile strength exhibited an increasing trend with the addition of nanocellulose, while the elongation at break showed the opposite trend. Moreover, it was demonstrated that the composite's thermal degradation shifts to higher temperatures with the addition of nanocellulose. The observed activation energies for the thermal degradation calculated using the Coats-Redfern method exhibited a significant increment for the composites reinforced with nanocellulose. These results show that the addition of nanocellulose into the PVA-alginate matrix enhances the chemical and thermal properties of the resulting hydrogel. All these improvements have resulted from more abundant and robust hydrogen bonds generated by the nanocellulose presence.